Analisis Pengaruh Tingkat Kesehatan Bank terhadap Perubahan Laba dengan Net Interest Margin (NIM) sebagai Variabel Intervening pada Bank Umum yang Terdaftar di BEI Periode 2013-2017 - Putri, Yochi Lajobhi; Tanjung, Amries Rusli; Savitri, Enni (Jurnal Ekonomi, 2019)
This research was conducted with the aim of empirically testing Net Profit Margin, Credit Risk Ratio, Non Performing Loans, Gross Profit Margin influencing changes in earnings at commercial banks listed on the Indonesia Stock Exchange Period 2013-2017. To analyze the net profit margin, credit risk ratio, non performing loans, gross profit margin affects the net interest margin (NIM) of commercial banks listed on the Indonesia Stock Exchange for the 2013-2017 period. Tests are carried out by path analysis with intervening variables. The results of this study indicate that; 1) net profit margin variables have no significant effect on earnings changes in commercial banks listed on the Indonesia Stock Exchange for the 2013-2017 period; 2) credit risk ratio, gross non- performing loan gross profit margin has a significant effect on changes in earnings at commercial banks listed on the Indonesia stock exchange for the 2013-2017 period; 3) net profit margin, non performing loan and gross profit margin have a significant effect on net interest margin (NIM) at commercial banks listed on the Indonesia Stock Exchange for the 2013-2017 period; 4) credit risk ratio does not have a significant effect on Net Interest Margin (NIM) at commercial banks listed on the Indonesia Stock Exchange for the 2013-2017 period; 5) net interest margin (NIM) has a significant effect on changes in earnings at commercial banks listed on the Indonesia Stock Exchange for the 2013-2017 period.